Chronic Lumbar Radiculopathy Treated With Autologous Peripheral Blood Stem Cells: A Case Report - Hadyanto Lim; AlexanderP.Marpaung; IndaM.Sinaga; Julenda Sebayang; Surjadi Rimbun; Adrian Khu (Jurnal Kedokteran Methodist, 2025)
Background : Lumbar radiculopathy may arise from the compression oflumbosacral nerve roots, leading to pain and disability. We report a caseof chronic lumbar radiculopathy that was successfully treated withperipheral blood stem cells over 24 weeks.Case Presentation : A 62-year-old woman with sharp pain in the back,radiating to both lower legs. Her pain became intense when she waswalking about 200 meters, and has been happening for 2 years. She felland hit her back 7 years ago, and refused to undergo spine surgery in ahospital. Magnetic resonance imaging revealed facet joint hypertrophyand thickening of the ligamentum flavum at L3/L4, L4/L5, and narrowingof the spinal canal. The pretreatment numerical pain rating (NPR) scorewas 7 (out of 10), and the Oswestry Disability Index (ODI) for low backpain was 19 or 38% (19/50 x100%). She was administered a 5-day courseof granulocyte colony-stimulating factor (G-CSF, 5mg/kg/day)subcutaneously, followed by leukapheresis on the fifth day. Circulatingand intravenous infusion of autologous peripheral blood stem cells wereanalyzed using flow cytometry. She also received transforaminal injectionsof 3 ml of peripheral blood stem cells (PBSCs) at each affected lumbarlevel. Peripheral blood CD34+ cells increased fro-treatment, the percentage reductions in pain and ODI were 100% and79.0%, respectively. There were no serious adverse effects from theprocedure.Conclusion: Autologous peripheral blood stem cells are an effectivetreatment for chronic lumbar radiculopathy.Keywords : lumbar radiculopathy, peripheral blood stem cells, spinalstenosis, granulocyte colony-stimulating factor, leukapheresis